Migraciones intrametropolitanas de los extranjeros: - Jordi Bayona i Carrasco; Fernando Gil-Alonso; Isabel Pujadas Rúbies (Cuadernos de Geografía de la Universitat de València)
The aim of this paper is to analyse internal migration patterns of foreigners in the two main Spanish metropolitan areas, Barcelona and Madrid. With this comparison we can observe similarities and differences in mobility patterns: demographic features of those moving seem to be similar in both urban areas, while the characteristics of their respective flows (intensity, origin and directions) present significant differences.